A Model Based Approach to School Shootings: Every Second Counts! - Arslan, Hasan T.; Olsen, Thomas (International Journal of Criminology and Sociology, 2016)
The cycle of violence invading our nation’s schools has necessitated the training of law enforcement agencies. A breakdown in communications could mean an incident spirals out of control and results in catastrophic unnecessary loss of lives. Active communication can be accomplished between officers and their superiors, so that decisions are made in a manner that best pursues a rapid end to the threat posed by the perpetrator, and a rapid extraction of the injured. Authors have developed an effective nine-step response model for law enforcement agencies after examination of the real-time cases, infamous school-shooting incidents, in the United States.